Role of a GAG Hinge in the Nucleotide-induced Conformational Change Governing Nucleotide Specificity by T7 DNA Polymerase - Jin, Zhinan (American Society for Biochemistry and Molecular Biology, 2011)
A nucleotide-induced change in DNA polymerase structure governs the kinetics of polymerization by high fidelity DNA polymerases. Mutation of a GAG hinge (G542A/G544A) in T7 DNA polymerase resulted in a 1000-fold slower rate of conformational change, which then limited the rate of correct nucleotide incorporation. Rates of misincorporation were comparable to that seen for wild-type enzyme so that the net effect of the mutation was a large decrease in fidelity. We demonstrate that a presumably modest change from glycine to alanine 20 Å from the active site can severely restrict the flexibility of the enzyme structure needed to recognize and incorporate correct substrates with high specificity. These results emphasize the importance of the substrate-induced conformational change in governing nucleotide selectivity by accelerating the incorporation of correct base pairs but not mismatches.